Electricity Consumption, Export and Production: Evidence from Malaysian Manufacturing Sector - Dzul Hadzwan, Husaini; Lean, Hooi Hooi (2012)
Study on the impact of energy on economic development becomes the new interest in the economy since the industrial revolution where greater amount of energy have been used in industrial production with high scale. Numeral studies have been done at the micro and macro levels to discover the role of energy and its impact on economic growth. However, little have been done to explore the essence of energy in a particular sector especially the energy based sector like manufacturing sector. This paper investigates the relationship between electricity consumption, export and production in Malaysia’s manufacturing sector in a multivariate framework. This study has two objectives. The first objective is to discover the existence of long-run relationship among the variables and the second objective is to examine the short-run causality among the variables. This is a time series analysis with the sample period covers from 1980-2010. Johansen and Juselius cointegration test is employed to discover the long-run relationship while Vector Error Correction Model (VECM) Granger causality test will be used to find out the causal relationship. We found that GDP of manufacturing sector, electricity consumption of the manufacturing sector, export of manufacturing sector, labor of the manufacturing sector and capital of the manufacturing sector are cointegrated in the long run. The VECM results show unidirectional causality running from electricity consumption of manufacturing sector to GDP of the manufacturing sector and from electricity consumption of manufacturing sector to labor of the manufacturing sector. Hence, these results indicate electricity is essential in the manufacturing sector. Keywords: Electricity consumption, output, Granger causality, cointegration